ChemInform Abstract: Copper(I)‐Catalyzed One‐Pot Synthesis of Highly Functionalized Pyrrolidines from Sulfonyl Azides, Alkynes, and Dimethyl 2‐(Phenylamino)maleate. Issue 22 (15th May 2015) - Ramanathan, Devenderan; Pitchumani, Kasi
Abstract: This cascade reaction consists of an azide—alkyne [3 + 2] cycloaddition/ring rearrangement, ketenimine formation, an intermolecular nucleophilic addition sequence and subsequent intramolecular cyclization followed by [1, 3]‐H shift.